EFEKTIVITAS MEDIA FLIP CHART DAN VIDEO PEMBELAJARAN DALAM MENINGKATKAN PEMAHAMAN TENTANG KARIES GIGI PADA ANAK KELAS V SD NEGERI KARANG JALAK 2 KOTA CIREBON (Jurnal Kesehatan Siliwangi, 2021)
Based on the Basic Health Research (RISKESDAS) in 2018, the prevalence of cavities in the people of Cirebon City was 34.45%, while for children aged 10-14 years, West Java Province, the prevalence of cavities was 39.80%. Many of these cases were found, one of which was at SDN Karang Jalak 2, besides that they had never been given counseling so that it was necessary to carry out dental and oral health counseling from an early age. The purpose of the study was to determine the effectiveness of flipchart media and instructional videos in increasing understanding of dental caries in fifth grade students at SDN Karang Jalak 2 Cirebon City, the subject of this study were 80 fifth grade students with total sampling technique. This type of research is a quasi-experimental. The results showed that the use of instructional video media was more effective than the use of flipchart media to increase understanding of dental caries with a difference of 0.75 more effective in increasing instructional video media, the difference in the pre-posttest value of learning videos was 51.75, while in the media flipchart is 51. The results of the Independent T-test show that there is a difference in the effectiveness of the two media in increasing understanding of dental caries with a value of p = 0.000 (p <0.05).